Protecting Consumers Against Defamation Claims: The Role of Common Interest in Product Reviews - Evi Kongres; Fajar Sugianto; Erny Herlin Setyorini; Bariyima Sylvester Kokpan; Sheng Zhang (Khazanah Hukum, 2024)
Consumers who post negative reviews of products on social media often face defamation claims by business entities. Such lawsuits have had a chilling effect on the right to freedom of expression, which is protected by law. In adjudicating consumer cases, judges have generally failed to apply the concept of common interest as a consideration, despite the potential benefits and awareness such reviews provide to prospective consumers. The common interest concept, as stipulated in defamation laws, can serve as a form of legal protection for consumers who post reviews on social media, provided the reviews are truthful, reflect actual conditions, and are made in good faith. By implementing the common interest concept and conducting its proper assessment, legal protection can be ensured for both consumers and businesses. Consumers would be shielded from unwarranted defamation claims, while businesses would be protected from malicious reviews by bad-faith consumers that result in financial or reputational harm. This study aims to dissect the legal safeguard afforded to consumers through the prism of common interest when confronting social media-based complaints or reviews ensnared in defamation litigations instigated by corporate entities. Employing a normative juridical methodology, the research amalgamates legislative analysis with conceptual frameworks. The research findings accentuate the significance of invoking the public interest doctrine in consumer-related litigation, thereby fortifying legal defenses against defamation allegations.